2011
DOI: 10.5152/tpd.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology Research of Blastocystis hominis in the Dokuz Eylül University Medical Faculty Hospital between 2005 and 2009

Abstract: As B. hominis was the most frequently seen parasite in patients with gastrointestinal complaints, we suggest that the parasite should be considered as pathogenic and sufficient attention must be paid in routine stool examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
(8 reference statements)
1
2
1
2
Order By: Relevance
“…Although it has been reported that maleness creates a statistically significant difference in the Blastocystis prevalence [29], there have also been studies demonstrating that there was a higher prevalence in females [30], or that there was no difference between the genders [25,26]. Similar to the study by Ertug et al [29], we identified a statistically significant relationship between the male gender and the Blastocystis-positivity (p = 0.020).…”
Section: Hemodialysis Patients P Valuesupporting
confidence: 82%
“…Although it has been reported that maleness creates a statistically significant difference in the Blastocystis prevalence [29], there have also been studies demonstrating that there was a higher prevalence in females [30], or that there was no difference between the genders [25,26]. Similar to the study by Ertug et al [29], we identified a statistically significant relationship between the male gender and the Blastocystis-positivity (p = 0.020).…”
Section: Hemodialysis Patients P Valuesupporting
confidence: 82%
“…Previous studies that were examined using different parasitological detection methods (Yaicharoen et al, 2005) or conducted in rural areas and in schools revealed a high prevalence of B. hominis (Warunee et al, 2007;Kitvatanachai et al, 2008). Other hospital-based studies may have shown a higher prevalence of blastocystosis compared to this study because those studies were conducted on patients with GI symptoms (Rostami Nejad et al, 2010;Gonzalez-Moreno et al, 2011;Inceboz et al, 2011;Paschke et al, 2011). FECT, as used for other protozoa and fecal parasites, generally appears to be unsuitable for B. hominis because it causes disruption of the organism (Stenzel and Boreham, 1996).…”
Section: Discussionmentioning
confidence: 62%
“…due to parasite form was determined as follow: Vacuolar form in 525 (67.49%), granular in 115 (14.78%), both vacuolar and granular in 138 (17.73%) cases. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%